Massive Neurilemoma of the Hard Plate in Which Preoperative Diagnosis Was Difficult - Masanori Kudoh; Hiroyuki Harada; Koshi Matsumoto; Yuriko Sato; Ken Omura; Yoshimasa Ishii (Case Reports in Surgery)
The patient was an 84-year-old man who was referred to our hospital in mid-December 2012 for a close examination of a mass arising from the left side of the hard palate that was found by a local dentist. The initial examination revealed the presence of a 3.0-cm elastic soft, dome-shaped mass in the left hard palate. CE-CT showed a lesion of size 1.8 × 1.4 cm in the right hard palate, which extended upward and invaded the nasal cavity. The mass was a solid tumor associated with resorption of surrounding bone and expansion of the greater palatine canal. CE-MRI indicated that the mass extended upward and invaded the nasal cavity, and the mass showed hypointensity on T1-weighted images, hyperintensity on T2-weighted images, and an irregular margin with internal enhancement. Abnormal uptake of FDG on PET-CT (SUVmax = 5.2) was observed in the left hard palate. The biopsy site lesion rapidly increased in size and biopsy was performed again in January 2013 due to suspicion of a malignant tumor. The histopathological diagnosis was a suspected malignant neurogenic tumor. Therefore, the patient underwent partial maxillectomy and a split-thickness skin graft in late February 2013. No recurrence was noted 29 months after the operation.